Utilization of refuse-derived fuel in industrial applications: Insights from Uttar Pradesh, India - Utsav Sharma; Dayanand Sharma; Amit Kumar; Tushar Bansal; Ankit Agarwal; Shudhanshu Kumar; Abid Hussian; Hesam Kamyab; Moinul Haq (Heliyon)
Urbanization and population growth in India have quickened, leading to an annual generation of around 62 million tonnes of municipal solid waste (MSW). Improper management of organic waste presents a major environmental problem due to air and water pollution, soil contamination and greenhouse gas production. This research aims to develop refuse-derived fuel (RDF) as a viable option, converting waste into a high-calorific energy carrier for industrial use. The RDF samples were collected from five strategic locations in Uttar Pradesh: Morta Site, Pipeline Site, and Sector 146 Noida, covering various waste compositions found at these landfill sites. Proximate and ultimate analyses of the RDF prepared from these sources were conducted, followed by in-depth Thermogravimetric Analysis (TGA) to validate its suitability as a potential feedstock. Careful waste segregation and treatment for better fuel quality can help minimize the difference in calorific values between different sites. Based on RDF tests, the waste-to-energy technology can divert over 30 % of solid waste from landfills and cut greenhouse gas emissions by as much as 25 % compared to traditional disposal methods. Unlike RDF, which is part of the replacement line for coal in industrial furnaces such as thermal power plants, it eliminates over 15 % and 20 % of sulfur dioxide (SO2) and nitrogen oxides (NOx). Ensuring that RDFs support sustainable energy technologies and align with circular economy principles, the study's results could enhance energy efficiency in waste management and complement environmental policy goals across all states in India and worldwide.